The Role of the Constitutional Court in Adjudicating Regional Election Disputes - Syukron Abdul Kadir; Jefrianus Tamo Ama (Edujavare Publishing, 2024)
The background to forming the Constitutional Court to carry out judicial reviews. The role of the Constitutional Court in ending election disputes is a form of democracy and legal reform in Indonesia. This research aims to investigate the role of the Constitutional Court in handling disputes that arise in the context of regional elections. This research uses a normative approach. All research results come from previous researchers. Therefore, the study of this scientific work is guided by existing secondary data from books, journals, and articles as reference material for the journal's description. The research results show that the role of the Constitutional Court, in this case, is a form of democracy and legal reform in Indonesia. Also, the constitutional court has a role in the democratization of Indonesia as a guardian of democracy, especially in constitutional review. So, the authority of the Constitutional Court in deciding disputes over election results is an authority contained in the third amendment to the 1945 Constitution. However, as the authority of the Constitutional Court develops, the authority of the Supreme Court is attached to the Constitution of the Supreme Court.